2004
DOI: 10.3201/eid1002.030610
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS Coronavirus in Patients with Suspected SARS

Abstract: Cases of severe acute respiratory syndrome (SARS) were investigated for SARS coronavirus (SARS-CoV) through RNA tests, serologic response, and viral culture. Of 537 specimens from patients in whom SARS was clinically diagnosed, 332 (60%) had SARS-CoV RNA in one or more clinical specimens, compared with 1 (0.3%) of 332 samples from controls. Of 417 patients with clinical SARS from whom paired serum samples were available, 92% had an antibody response. Rates of viral RNA positivity increased progressively and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
251
1
18

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(288 citation statements)
references
References 14 publications
16
251
1
18
Order By: Relevance
“…Ferrets shed virus from the upper respiratory tract in a similar way to human SARS patients (Chan et al, 2004). As shown in Fig.…”
Section: Nasal Virus Sheddingmentioning
confidence: 72%
“…Ferrets shed virus from the upper respiratory tract in a similar way to human SARS patients (Chan et al, 2004). As shown in Fig.…”
Section: Nasal Virus Sheddingmentioning
confidence: 72%
“…Northern blotting showed that ACE2 mRNA is expressed abundantly in endothelial cells of the heart, kidneys, and testis (37). In addition, RT-PCR and immunocytochemistry showed that ACE2 mRNA and protein are expressed on oral, nasal, and intestinal mucosa, alveolar epithelial cells in lung, stomach, skin, lymph nodes, thymus, bone marrow, spleen liver, kidney, and brain, and arterial and venous endothelial cells and arterial smooth muscle cells in many organs (38)(39)(40)(41). These sites for ACE2 expression include most of the sites for SARS-CoV replication in autopsy specimens (26).…”
Section: Discussionmentioning
confidence: 99%
“…At this juncture, the newer generation of real-time PCR performed on NPAs is expected to have a sensitivity of y80% [41,42]. Later in the disease, viral RNA could also be detected in other specimens, such as stool and urine [36]. Following optimisation, the detection limit of real-time PCR is around 10 RNA copies per reaction.…”
Section: Virological Diagnosis Of Severe Acute Respiratory Syndromementioning
confidence: 99%
“…In equivocal cases, such as the recent laboratory-acquired situations, they could be valuable for establishing the diagnosis. Viral culture is still insensitive [36] and, again, suffers from the drawback of taking too long for bedside decisions. Hence, much effort has been put into the development and evaluation of rapid tests that yield a result within hours.…”
Section: Virological Diagnosis Of Severe Acute Respiratory Syndromementioning
confidence: 99%
See 1 more Smart Citation